The Design of Quartet Card Game Integrated with Augmented Reality for Sharf (Morphology) Learning Media - Khoirunnisa, Tsania; Ahsanuddin, Mohammad (Arabiyatuna: Jurnal Bahasa Arab, 2024)
This study aimed to describe the stages of making and feasibility of quartet cards integrated with augmented reality as Sarf learning media. Sarf is an element of grammar in Arabic learning and a study that discusses the rules in Arabic. The creation of this media was undertaken due to several challenges in learning Sarf, including a) the rapidly changing discussion topics, b) the difficulty of memorizing the material, c) numerous alterations in word patterns, and d) the infrequent use of changing vocabulary in daily life. These challenges necessitated that teachers become more creative and innovative to simplify the mastery of Sarf material for students, one method being the implementation of learning strategies through play. This strategy certainly required a medium to make the learning of Arabic more interactive and meaningful. Therefore, through this research, which was research and development, the researchers developed a quartet card game media that could facilitate students in learning Sarf material using the ADDIE approach. Data collection methods used observation, questionnaires, and literature studies. The data analysis techniques in this study were adjusted to the type of research data. The result of this research was the development of quartet card game media and applications as augmented reality markers. Based on the validation results, the percentage of material and media validation showed an average of 82.75% and 89.88%, respectively, so that the media was declared feasible to be tested with some minor revisions. Meanwhile, the results of student and teacher response tests showed 87.65% and 84.70%, respectively, so that the media was declared practical after being tested in classroom learning.